Material selection of sustainable composites by the valorisation of plastics and agro wastes: An integrated q-rung orthopair fuzzy-based multiple criteria decision making model - Ashish Soni; Sonu Kumar Gupta; Dai-Viet N. Vo; Natarajan Rajamohan; Mohammad Yusuf (Elsevier BV, 2026)
The concern for plastic wastes and high usages for building construction materials has promoted the nation towards eco-friendly composite materials for structural components. Anappropriate choice of material improves the functionality and life cycle of a product . The research seeks to promote sustainable practices in building construction for the attainment of the circular economy. This investigation anticipated a fuzzy number-based integrated Stepwise Weight Assessment Ratio Analysis (SWARA)-Complex Proportional Assessment (COPRAS) mathematical model for material selection of eco-friendly composites. In the present work, eight (08) different composites are developed by recycling of waste plastics namely low-density polyethylene, high-density polyethylene, polypropylene, and polyethylene terephthalate with the reinforcement of natural fibres of coconut and jute. The alternatives are ranked by considering seven (07) criteria for structural application such as floor tiles, pavements, panels, etc. The compressive is identified as the most significant while hardness is least preferable criteria for composite having structural applications. The proposed model has identified the alternatives A6 and A1 as the most and least preferable alternatives, respectively. The research has recommended the incorporation of 20 wt.% of jute fibre with 80 wt.% of polypropylene in composites for structural applications. The comparative analysis of rankings against the other well-known techniques has verified the trustworthiness of the model. The high ranges of 0.76–-0.928 for Spearman’s rank correlations coefficient has verified the robustness of the ranking results. The sensitivity analyses have shown the influence of criteria weight on rankings. The suggested mathematical approach can efficiently rank the composites and address the challenges associated in the material selection of polymeric composites in unpredictable environments.
Keywords: Material selection; Mathematical model; Plastic wastes; Recycling; Sustainable composites